2011
DOI: 10.1177/1534735411400311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Music Therapy Intervention on Autonomic Function in Anthracycline-Treated Breast Cancer Patients

Abstract: Anthracyclines are potent antineoplastic agents associated with cardiotoxicity, which may lead to congestive heart failure, causing impairment of autonomic cardiovascular function as assessed by heart rate variability (HRV). This decreases survival rates. This study aimed to determine whether music therapy intervention improves autonomic function in anthracycline-treated breast cancer patients, and if so, whether such improvements persist after cessation of the intervention. Participants were 12 women with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
1
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 22 publications
3
57
1
7
Order By: Relevance
“…[1] A previous study demonstrated that auditory stimulation with a relaxant musical style two hours per day, two days per week over eight weeks improved cardiac autonomic regulation in subjects treated with a cardiotoxic drug; [2] however, its acute effects are still controversial. [1] Conversely, heavy metal musical style was indicated to present negative effects that are associated with stress, including sleep disorders, fatigue, exhaustion, and immunologic activity impairment.…”
mentioning
confidence: 99%
“…[1] A previous study demonstrated that auditory stimulation with a relaxant musical style two hours per day, two days per week over eight weeks improved cardiac autonomic regulation in subjects treated with a cardiotoxic drug; [2] however, its acute effects are still controversial. [1] Conversely, heavy metal musical style was indicated to present negative effects that are associated with stress, including sleep disorders, fatigue, exhaustion, and immunologic activity impairment.…”
mentioning
confidence: 99%
“…In contrast, a different style of relaxant music was reported to chronically increase the parasympathetic modulation of the heart [2]. The authors observed that music therapy during eight months with popular Taiwanese songs with moderate, pleasant rhythms and tempos improved HRV of the patients treated with an anti-neoplasic cardiotoxic drug.…”
Section: Discussionmentioning
confidence: 84%
“…The common intensity used to induce a startle reflex is 110 dB, and this intensity is much louder than environmental noise. Nevertheless, subjects repeatedly exposed to between 60 dB and 110 dB white-noise stimuli were seen to become habituated over time with regard to their cardiac response [1,2,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations